2017
DOI: 10.1111/ajco.12802
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes of melanoma in Asia: Results from the National Cancer Centre Singapore

Abstract: Our study reinforces the known unique clinicopathologic features of melanomas in Asians where AM and MM predominate. Age and stage remain the most critical prognostic factors across all subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Recently study has revealed high expression levels of IL22 in both lung tumors and serum of patients with lung cancer, promoteing Kras mutant lung tumorigenesis 20 . Cutaneous melanoma is obviously different from ocular melanoma and mucosal melanoma in epidemiological features, clinical characteristics, treatment and outcomes 29,30 . Although the direct impact and molecular mechanisms of interleukin 22 on human malignancies had been extensively investigated in a great number of previous studies, few report aim at the direct role of interleukin 22 on cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently study has revealed high expression levels of IL22 in both lung tumors and serum of patients with lung cancer, promoteing Kras mutant lung tumorigenesis 20 . Cutaneous melanoma is obviously different from ocular melanoma and mucosal melanoma in epidemiological features, clinical characteristics, treatment and outcomes 29,30 . Although the direct impact and molecular mechanisms of interleukin 22 on human malignancies had been extensively investigated in a great number of previous studies, few report aim at the direct role of interleukin 22 on cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, these previous studies comprised mainly white populations, in which SSM and LMM are the major clinical types of melanoma. 4 In contrast, Asians manifest a distinct clinicopathological type of melanoma from that of whites and show much higher frequencies of ALM and MUC, [4][5][6][7] which have been shown to be less susceptible to immune checkpoint inhibitors. 8 Although aPD-1mAb and ipilimumab have demonstrated their efficacy in single-arm studies, 9,10 no comparative studies have been published showing improvement of OS by immune checkpoint inhibitors in Asian melanoma patients.…”
Section: Case Reportmentioning
confidence: 99%
“…Ocular melanomas are a group of uncommon cancers 1 , and account for approximately 5% of melanoma cases 2 . More than three-quarters of ocular melanomas involve the uvea, with the remainder of cases arising from the conjunctiva 3 . Uveal melanomas (UM) can arise from any part of the uveal tract, including the choroid, iris and ciliary body.…”
Section: Introductionmentioning
confidence: 99%